Syngas production from ethanol dry reforming using Cu-based perovskite catalysts promoted with rare earth metals - Attili, Ramkiran; Vo, Dai-Viet N.; Mohd Sabri, Mahmud (Elsevier Ltd, 2021)
This paper reports about the production of syngas from dry reforming of ethanol (EDR) upon LaCuO3 and CeCuO3 catalysts that were prepared by using citrate sol-gel method. EDRs were run with fresh catalyst at each varied variable and 42 L/gcat/h of feed in a tubular reactor under atmospheric pressure. At equal feed pressure of reactants, steady state CO2 conversion increased exponentially from 700 to 800 °C while H2 and CO yields were increasing differently in sigmoid trend rendering H2/CO ratios to drop linearly from 1.7 to 1.0. However, these reaction results except the latter are otherwise when ethanol-CO2 ratio was increased (reducing CO2 pressure) at 750 °C. A minimum H2/CO ratio was evidenced at the ethanol-CO2 ratio of 1.48. LaCuO3 catalyst was more superior in producing syngas owing to its relatively low reduction temperature, high surface area and crystallinity, many active sites, good surface morphology and many C–O, C–H and hydroxyl groups.